EFFECTIVENESS OF SOME PLANT PRODUCT FOR THE CONTROL OF PULSE BEETLE CALLOSOBRUCHUS CHINENSIS ON STORED GREEN GRAM - SINGH, S.C.; BHAR, N.K. MAHARAJ (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
The effect of castor and karanji oil at 25, .50, .75 and 1.0% w/w concentration/ 100g of green gram against pulse beetle C. chinensis were studied. The study revealed encouraging results as the seeds of green gram could effectively be protected from the damage by mixing the seed at the rate of 25 to 1.0 ml/100g seed. The study suggested these oils to be pest effective, safer to predators, economically viable and Socially acceptable especially by the farmers of the region.